Growth Performance and Profitability of Broilers Chickens with Vermi meal Supplementation under Total Confinement Management - Marcos Erram Bollido (Jurnal Ilmu Pertanian Indonesia, 2021)
This study was conducted to determine the growth performance and profitability of broilers chicken with vermi meal supplementation under a total confinement management system. A total of 60 broiler chickens were randomly distributed to four dietary treatments: T1= commercial feed (CF), T2= CF+2% vermi meal (VM), T3= CF+3% VM, T4= CF+5% VM inclusion in a completely randomized design. Feed conversion ratio was not significantly influenced by VM supplementation. However, the highest feed intake was recorded in broilers fed CF supplemented with 2% VM (T2) while control broilers fed only CF (T1) had the lowest feed consumption. Broiler chickens fed CF supplemented with 2% VM (T2) were recorded with the highest values of final body weight and weight gain compared to T1 group and T4 group, respectively. However, broiler in T2 group had similar values of body weights and weight gains compared to T3. Consequently, 2% level of VM had an optimum result in final weight, weight gain, and feed consumption, while comparable to the other treatments in water consumption, feed conversion ratio, dressing percentage, and carcass weight. Cost and return analysis of the dietary treatments with VM showed a negative effect, since the higher concentration of VM supplementation had the higher cost in production, due to the expensive price of imported vermin or earthworm meal. Keywords: broiler chickens, performance, total confinement, vermi meal